Histopathological Characteristics And Incidence Of Thyroid Carcinoma In A Tertiary Care Hospital In Pakistan: A Cross-Sectional Study (Journal of Pharmaceutical Negative Results, 2020)
Background: The amelioration of thyroid cancer as the most frequently occurring malignancy of endocrine organs has been recorded with an increasing number of cases, especially for papillary thyroid carcinomas (PTC). The population growth, as a consequence, has intensified the public health alarm. Besides these, there is a group of thyroid cancers including follicular, medullary, and anaplastic, which exhibits stable incidence rates during different periods. Hence, proficient diagnosis and treatment of early stages are necessary. Objectives: The study aims to assess the histopathology features and incidence of thyroid carcinoma among patients who receive treatment at our tertiary care hospital in Pakistan. In our study, we concentrate on classifying the cases of different types of thyroid cancers as well as examining the distribution and prevalence of these cancers over the last five years.Study design: A cross-sectional study.Place and duration of study. Department of pathology Watim medical and dental college, Rawat from 05 July 2017 to 05 June 2020 MethodsThe cross-sectional study was done for this work in the Pathology Department of Rai Medical College Sargodha from July 2017 to June 2020. From the total 187 thyroid lesions reviewed, 28 pathology reports were identified as malignant. Samples of biopsy were obtained and histopathologically assessed by using hematoxylin and eosin staining. There were four kinds of carcinoma (which had different types of morphological features) that were papillary, follicular, medullary, and anaplastic. Demographic data of patients such as age and gender were also obtained. Histologically specimens were prepared and examined by experienced pathologists to ensure correct diagnosis. The incidence and the geographic disparity patterns were analyzed statistically. The types of thyroid carcinoma were classified.ResultsThe analysis was conducted on 187 thyroid lesions. Based on the findings, 28 were diagnosed malignant which represents a percentage of 14. 97%. Oct 3:: The most common malignant tumor of the thyroid was papillary thyroid carcinoma (PTC), which was found in 22 cases (74. 8%). Follicular thyroid carcinoma (FTC) took 3 cases (11,2%), medullary thyroid carcinoma (MTC) – 2 cases (10,4%), and anaplastic thyroid carcinoma (ATC) – 1 case (4,6%). The age range of patients was 30-65 years, with a female-to-male ratio of 3:A. High incidence rates of PTC around the world are similar to the global tendency, whereas the cases of other types stayed constant. This data will reflect the recognition of management strategies for PTC which will be most effective.ConclusionThe Study article argues that the vast majority of papillary thyroid cancer cases are present among our population. Interestingly, there has been a stable trend in the rate of other thyroid malignancies. However, precise diagnostic and therapeutic approaches towards PTC management are of the essence. Additionally, it is necessary to study the hidden factors which are a contributing factor.